Strategi Diferensiasi Pada Pt Matahari Department Store Tbk - Shieni Shieni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The aim of this research is to explain the differentiation strategies of PT Matahari Department Store Tbk to attract customers. This will be done through a discussion and analysis of all five of the differentiation strategies which are; product, service, personnel, channel and image. The theoretical framework gives an overview of the differentiation strategies; it also provides the reader with a description of consumer decision process, competitive advantage, strategic customer and key competitors. The methodology chapter provides a description of the method choices for this research; this study is done by a qualitative approach. The analysis chapter provides the differentiations strategies that are mentioned in the theoretical framework. The conclusion will conclude the analysis of the theoretical parts of this thesis and answer the research question. The needed future improvements will be discussed closely in the suggestion.